Cutting Edge: Latecomer CD8 T Cells Are Imprinted with a Unique Differentiation Program - D'Souza, Warren N. (2006)
Factors that influence T cell responses, such as Ag load, APCs, costimulatory molecules, and cytokines, dramatically change during the course of an immune response. We observed that antiviral CD8 T cells were not recruited from circulation simultaneously, but over a period of 3–4 days. Consequently, locally resident T cells and those that entered secondary lymphoid tissue later were primed in very different environments. The cells recruited later in the response were imprinted with a unique differentiation program, such that their magnitude of proliferation was reduced and their kinetics of expansion was delayed. In addition, we found that the “latecomer” CD8 T cells displayed a unique surface phenotype indicative of reduced stimulation but were not preferentially recruited into the surviving pool of memory cells. This finding demonstrates that the timing of recruitment of individual T cell clones determines the population dynamics of the subsequent immune response.